Developing a community-level anti-HIV/AIDS stigma and homophobia intervention in new York city: The project CHHANGE model. (August 2017) - Frye, Victoria; Paige, Mark Q.; Gordon, Steven; Matthews, David; Musgrave, Geneva; Kornegay, Mark; Greene, Emily; Phelan, Jo C.; Koblin, Beryl A.; Taylor-Akutagawa, Vaughn
Highlights: HIV stigma and homophobia are associated with negative health and social outcomes. Few interventions address both HIV stigma and homophobia at the community level. CHHANGE is a community-level, multicomponent program to reduce stigma and homophobia. CHHANGE promoted gay space; trained residents to interrupt stigma and ran bus ads. CHHANGE was feasible, acceptable, and applied novel, intersectional approaches. Abstract: HIV/AIDS stigma and homophobia are associated with significant negative health and social outcomes among people living with HIV/AIDS (PLWHA) and those at risk of infection. Interventions to decrease HIV stigma have focused on providing information and education, changing attitudes and values, and increasing contact with people living with HIV/AIDS (PLWHA), activities that act to reduce stereotyped beliefs and prejudice, as well as acts of discrimination. Most anti-homophobia interventions have focused on bullying reduction and have been implemented at the secondary and post-secondary education levels. Few interventions address HIV stigma and homophobia and operate at the community level. Project CHHANGE, Challenge HIV Stigma and Homophobia and Gain Empowerment, was a community-level, multi-component anti-HIV/AIDS stigma and homophobia intervention designed to reduce HIV stigma and homophobia thus increasing access to HIV prevention and treatment access. The theory-based intervention included three primary components: workshops and trainings with local residents, businesses and community-based organizations (CBO); space-based events at a CBO-partner drop-in storefront and "pop-up" street-based events and outreach; and a bus shelter ad campaign. This paper describes the intervention design process, resultant intervention and the study team's experiences working with the community. We conclude that CHHANGE was feasible and acceptable to the community. Promoting the labeling of gay and/or HIV-related "space" as a non-stigmatized, community resource, as well as providing opportunities for residents to have contact with targeted groups and to understand how HIV stigma and homophobia relate to HIV/AIDS prevalence in their neighborhood may be crucial components of successful anti-stigma and discrimination programming.